2006
DOI: 10.1007/s10162-006-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging by Atomic Force Microscopy of the Plasma Membrane of Prestin-Transfected Chinese Hamster Ovary Cells

Abstract: The high sensitivity of mammalian hearing is achieved by amplification of the motion of the cochlear partition. This cochlear amplification is thought to be generated by the elongation and contraction of outer hair cells (OHCs) in response to acoustical stimulation. This motility is made possible by a membrane protein embedded in the lateral membrane of OHCs. Although a fructose transporter, GLUT-5, was initially proposed to be this protein, a later study identified the gene of the motor protein distributed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
19
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
(37 reference statements)
5
19
0
Order By: Relevance
“…This was supported by AFM observation of similar sized particles on the surface of Chinese hamster ovary cells in which prestin was heterologously expressed (24). The diameter of the particles was reported 8 -15 nm, with the highest population at 11 nm (22)(23)(24).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This was supported by AFM observation of similar sized particles on the surface of Chinese hamster ovary cells in which prestin was heterologously expressed (24). The diameter of the particles was reported 8 -15 nm, with the highest population at 11 nm (22)(23)(24).…”
Section: Discussionsupporting
confidence: 52%
“…This was supported by AFM observation of similar sized particles on the surface of Chinese hamster ovary cells in which prestin was heterologously expressed (24). The diameter of the particles was reported 8 -15 nm, with the highest population at 11 nm (22)(23)(24). The dimensions presented in this study (77 Å in side length at the widest cytoplasmic region and 96 Å in diagonal length) agree with the previous observations; therefore, we conclude that the prestin molecules presented in this study correspond to individual particles on the OHC lateral membrane.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The lateral membrane has also been observed by atomic force microscopy (AFM) and the existence of many particles with diameters of about 10 nm has also been reported [17]. Imaging by AFM of prestin-transfected Chinese hamster ovary (CHO) cells has revealed that particle-like structures 8-12 nm in diameter are possibly prestin [18]. However, since there are many kinds of intrinsic membrane proteins other than prestin in the plasma membranes of OHCs and CHO cells, it was impossible to clarify which structures observed in such membranes were prestin.…”
Section: Introductionmentioning
confidence: 94%
“…Mutational studies have suggested that prestin is a glycosylated protein (11) and is phosphorylated (12) . It has also been indicated that prestin exists as tetramers (13) , which form particles with a diameter of 8-12 nm (14) (15) .…”
Section: Introductionmentioning
confidence: 99%